State of war the secret history of the CIA and the Bush administration - Risen, James (Free Press, 2006)
With relentless media coverage, it is hard to believe that we still might not know some of the most significant facts about the presidency of George W. Bush. Yet beneath the surface events of the Bush presidency lies a secret history that involves domestic spying, abuses of power, and outrageous operations. It includes a CIA that became caught in a political crossfire that it could not withstand, and what it did to respond. It includes a Defense Department that made its own foreign policy, even against the wishes of the commander-in-chief. It features a president who created a sphere of deniability in which his top aides were briefed on matters of the utmost sensitivity--but the president was carefully kept in ignorance. Based on extraordinary sources in Washington and around the world, this book exposes an explosive chain of events and a series of troubling patterns.--From publisher description.